A hydrogen production anode catalyst slurry and anode catalyst layer and membrane electrode using the same
By using a solvent system combining an aqueous solvent, a high-alcohol and dimethyl sulfoxide, an anode catalyst slurry for hydrogen production was prepared for water electrolysis, which solved the problem of easy cracking of the anode catalytic layer and improved structural stability and hydrogen production efficiency.
Patent Information
- Application Number
- CN202411997139.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
During the hydrogen production process of water electrolysis, cracks are prone to occur in the anode catalytic layer, which affects the performance and life of the fuel cell.
A combination of aqueous solvents, higher alcohols and dimethyl sulfoxide (DMSO) were used as solvents to prepare a hydrogen production anode catalyst slurry. By uniformly dispersing the dispersant polymer and the anode catalyst, a tighter anode catalyst layer is formed to reduce cracks.
It effectively improves the structural stability of the anode catalytic layer, reduces the occurrence of cracks, and improves the mechanical stability and hydrogen production efficiency of the membrane electrode.
Smart Images

Figure CN119776906A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and specifically relates to a hydrogen production anode catalyst slurry and an anode catalyst layer and a membrane electrode using the same. Background Art
[0002] Hydrogen production by water electrolysis is a method of using electricity to decompose water into hydrogen and oxygen. It is coupled with renewable energy sources such as wind and solar energy to produce green hydrogen, and is one of the most promising technologies. The anion exchange membrane water electrolysis (AEMWE) process has the advantages of low cost, fast start and stop, and low energy consumption. It combines the low-cost material system of alkaline water electrolysis technology and achieves the high hydrogen production efficiency of proton exchange membrane water electrolysis (PEMWE). The membrane electrode is a key component of the electrolyzer. It consists of a gas diffusion layer, a catalyst layer, and an anion exchange membrane. It is the reaction site and important flow channel of the substance. The catalyst layer in the membrane electrode is even more important. The catalyst layer has an important influence on the performance and life of the membrane electrode. The distribution state of the catalyst particles determines the gas and ion transmission capacity of the membrane electrode. Therefore, the reasonable construction of the catalyst layer will be one of the important topics in the development of fuel cells, especially the reasonable construction of the anode catalyst layer.
[0003] Affected by the boiling point, dielectric constant, surface tension and other properties of the slurry solvent, the anode catalyst layer is prone to cracking. Cracks in the anode catalyst layer will seriously affect the performance of the fuel cell, such as accelerating the aging of the proton membrane, and the cracked area is prone to water flooding, thereby accelerating the degradation of the membrane electrode performance.
[0004] Conventional catalyst slurry is mainly composed of low-level alcohol as solvent, while the proton / anion exchange membrane is a high molecular weight ionomer. Directly coating the catalyst slurry on the surface of the proton / anion exchange membrane is prone to swelling, resulting in defects such as cracks in the catalyst layer. Summary of the invention
[0005] The object of the present invention is to provide a hydrogen production anode catalyst slurry and an anode catalyst layer and a membrane electrode using the same, wherein the hydrogen production anode catalyst slurry can effectively improve the solvent volatilization during the preparation of the anode catalyst layer, improve the structural stability of the prepared anode catalyst layer, and reduce cracks in the anode catalyst layer.
[0006] According to a first aspect of the present invention, a hydrogen production anode catalyst slurry is provided, comprising an anode catalyst, an ionomer, and a solvent, wherein the solvent comprises an aqueous solvent, a higher alcohol, and dimethyl sulfoxide (DMSO), wherein the number of carbon atoms in the higher alcohol is not less than 3; the mass ratio of the higher alcohol to the aqueous solvent is 1 to 7:1, and the mass of dimethyl sulfoxide: the sum of the mass of the aqueous solvent and the higher alcohol = 3:7 to 57.
[0007] The hydrogen production anode catalyst slurry provided by the present invention adopts a combination of aqueous solvent, higher alcohol and dimethyl sulfoxide as the solvent, which can improve the structural stability of the anode catalyst layer prepared by the hydrogen production anode catalyst slurry, and can effectively improve the solvent volatilization in the process of preparing the anode catalyst layer, thereby greatly reducing the membrane shrinkage caused by solvent volatilization, and effectively improving the crack problem of the anode catalyst layer.
[0008] On the one hand, the use of a solvent system composed of an aqueous solvent, a higher alcohol and dimethyl sulfoxide (DMSO) cleverly matched to form a solvent system can promote the uniform dispersion of ionomers and anode catalysts in the hydrogen production anode catalyst slurry, so that the ionomers are more evenly attached to the catalyst surface, and can reduce the degree of agglomeration of catalyst particles in the slurry, which is conducive to reducing the average particle size in the hydrogen production anode catalyst slurry, thereby enabling the hydrogen production anode catalyst slurry to form a tighter anode catalyst layer, which helps to improve the mechanical stability of the membrane electrode and reduce wear and fall off during the hydrogen production process. On the other hand, the use of aqueous solvents, higher alcohols and dimethyl sulfoxide that meet the above mass ratio requirements can increase the exposure rate of the activation sites of the anode catalyst, help more activation sites to be exposed, and can shorten the transmission distance of gas and water molecules inside the anode catalyst layer, thereby improving the hydrogen production efficiency. At the same time, by using higher alcohols with a carbon atom number of not less than 3 and adjusting the feed mass ratio of dimethyl sulfoxide to aqueous solvent and higher alcohol, dimethyl sulfoxide accounts for 5-30% of the solvent system, thereby improving the volatilization of alcohols, thereby reducing membrane shrinkage caused by solvent volatilization, effectively improving the cracks in the anode catalyst layer, and enhancing the structural stability of the anode catalyst layer.
[0009] Preferably, the higher alcohol includes at least one of propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, benzyl alcohol, propylene glycol, glycerol, and n-pentanol. The selection of the above-mentioned higher alcohols can not only improve the solvent volatilization and enhance the structural stability of the anode catalyst layer during the preparation of the anode catalyst layer, but also improve the compatibility of the solvent with the catalyst and the ionomer, thereby forming a hydrogen production anode catalyst slurry that is evenly dispersed and not easy to agglomerate.
[0010] Preferably, the aqueous solvent comprises water.
[0011] Preferably, the anode catalyst includes at least one element selected from the group consisting of ruthenium, iridium, nickel, iron, cobalt and manganese.
[0012] Preferably, the anode catalyst includes an oxide containing at least one element selected from the group consisting of ruthenium, iridium, nickel, iron, cobalt and manganese.
[0013] Preferably, the hydrogen production anode catalyst slurry further includes an additive, and the additive includes at least one of hydrolyzed polyacrylamide, polyethylene oxide, hydroxymethyl cellulose sodium salt, and hydroxyethyl cellulose. Introducing the above-mentioned additive into the hydrogen production anode catalyst slurry can change the rheological properties of the hydrogen production anode catalyst slurry, which is beneficial to subsequent processing to improve the preparation yield and production efficiency of the anode catalyst layer.
[0014] Preferably, the additive accounts for no more than 1 wt % of the mass of the hydrogen production anode catalyst slurry.
[0015] Preferably, the viscosity of the hydrogen production anode catalyst slurry is 10 to 200 cP.
[0016] Preferably, the solid content of the hydrogen production anode catalyst slurry is 5 to 30 wt%. Generally speaking, the higher the solid content of the slurry, the worse the dispersibility. However, by using the above-mentioned solvent, the present solution can make the hydrogen production anode catalyst slurry have good dispersibility at a higher solid content, and it is not easy to agglomerate or settle. In addition, the obtained anode catalyst layer has fewer cracks and better structural stability.
[0017] According to the second aspect of the present invention, a method for preparing the above-mentioned hydrogen production anode catalyst slurry is provided, comprising the following operations: firstly, the ionomer is uniformly mixed with the solvent to obtain a first dispersion, then, the first dispersion is uniformly mixed with the anode catalyst, and after post-treatment, the hydrogen production anode catalyst slurry is obtained. By first dispersing the ionomer, the ionomer branch chain is fully extended, and then the anode catalyst is introduced into the slurry system, so that the ionomer can be more uniformly attached to the surface of the anode catalyst, thereby not only reducing the degree of agglomeration of catalyst particles in the slurry, but also improving the anti-sedimentation property of the hydrogen production anode catalyst slurry, thereby improving the structural stability of the anode catalyst layer, reducing the cracking in the process of preparing the anode catalyst layer, and forming more active sites, thereby improving the hydrogen production efficiency of the membrane electrode using the hydrogen production anode catalyst slurry. In addition, it should be noted that there is also a slurry mixing process in the industry, which specifically includes mixing ionomers with solvents to form ionomer solutions, mixing catalysts with solvents to form catalyst solutions, and then mixing ionomer solutions with catalyst solutions to form catalyst slurries. This slurry mixing process is often used to prepare low-solid slurries. If the slurry viscosity is to be increased, a binder is required. The above-mentioned method for preparing hydrogen production anode catalyst slurry adopts a step-by-step feeding method of first dispersing the ionomer and then adding the anode catalyst. A hydrogen production anode catalyst slurry with moderate viscosity, high solid content and good dispersibility can be obtained without additives or binders.
[0018] Preferably, the post-treatment includes: shearing and cell crushing the second dispersion obtained by mixing the first dispersion with the anode catalyst.
[0019] Preferably, the post-treatment further comprises: uniformly mixing the third dispersion obtained after shearing and cell crushing with an additive.
[0020] Preferably, the post-treatment further comprises: filtering and defoaming the fourth dispersion obtained by mixing the third dispersion with the additive.
[0021] According to a third aspect of the present invention, an anode catalyst layer is provided. The anode catalyst layer is made from the above-mentioned hydrogen production anode catalyst slurry.
[0022] Preferably, the preparation method of the anode catalyst layer includes the following operations: coating the hydrogen production anode catalyst slurry on the anion exchange membrane, and drying it under the condition of 50 to 80 ° C, so that the hydrogen production anode catalyst slurry forms an anode catalyst layer. By drying and curing the hydrogen production anode catalyst slurry at a drying temperature of 50 to 80 ° C to form an anode catalyst layer, the solvent volatilization of the hydrogen production anode catalyst slurry can be further improved, the possibility of cracking of the anode catalyst layer can be reduced, the flatness of the catalyst layer can be improved, and defects such as cracks and mottles can be reduced. In addition, the longer the hydrogen production anode catalyst slurry stays on the anion exchange membrane, the greater the damage of the organic solvent to the anion exchange membrane. By using a solvent composed of an aqueous solvent, a higher alcohol and dimethyl sulfoxide, and drying it at the above-mentioned drying temperature, the hydrogen production anode catalyst slurry can be completely leveled, and the wet film state can be shortened, reducing the damage of the organic solvent to the anion exchange membrane.
[0023] Preferably, coating comprises at least one coating method selected from the group consisting of blade coating, roller coating, and slot extrusion coating.
[0024] According to a fourth aspect of the present invention, a membrane electrode is provided, comprising an anode gas diffusion layer, an anode catalyst layer, an anion exchange membrane, a cathode catalyst layer, and a cathode gas diffusion layer arranged in sequence; the anode catalyst layer comprises the above-mentioned anode catalyst layer. By adopting the above-mentioned anode catalyst layer, this solution can improve the structural stability of the membrane electrode and improve the overall performance of the membrane resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic diagram for recording the crack rate of the anode catalyst layer provided in Example 1;
[0026] Figure 2 A metallographic microscope image of the anode catalyst layer provided in Example 1;
[0027] Figure 3 A metallographic microscope image of the anode catalyst layer provided for Example 9;
[0028] Figure 4 This is a metallographic microscope image of the anode catalyst layer provided for Comparative Example 1. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0030] Example 1
[0031] (1) Hydrogen production anode catalyst slurry
[0032] The raw material composition of the hydrogen production anode catalyst slurry is shown in Table 1.
[0033] Table 1. Raw material composition of hydrogen production anode catalyst slurry
[0034]
[0035] According to the above table, water is an aqueous solvent and n-butanol is a higher alcohol. According to the mass ratio, n-butanol: water = 4:1, dimethyl sulfoxide: (n-butanol + water) = 3:17. Therefore, the mass proportion of dimethyl sulfoxide in the solvent is 15wt%.
[0036] The method for preparing hydrogen production anode catalyst slurry includes the following operations: firstly, uniformly mixing an ionomer and a solvent to obtain a first dispersion, then uniformly mixing the first dispersion and an anode catalyst to obtain a second dispersion; performing shearing and cell crushing to obtain a third dispersion, uniformly mixing the four dispersions and an additive to obtain a fourth dispersion, then performing filtering and degassing treatment to obtain hydrogen production anode catalyst slurry.
[0037] (2) Anode catalyst layer and membrane electrode
[0038] The membrane electrode comprises an anode gas diffusion layer, an anode catalyst layer, an anion exchange membrane, a cathode catalyst layer and a cathode gas diffusion layer which are stacked in sequence, wherein the anode catalyst layer is made of the above-mentioned hydrogen production anode catalyst slurry.
[0039] The method for preparing the anode catalyst layer comprises the following operations: coating the hydrogen production anode catalyst slurry on the anion exchange membrane and drying it at 65° C. to form the anode catalyst layer from the hydrogen production anode catalyst slurry.
[0040] The preparation method of the membrane electrode includes the following operations: stacking the cathode gas diffusion layer, the cathode catalyst layer, the anion exchange membrane, the anode catalyst layer, and the anode gas diffusion layer in sequence, and tightening them at a pressure of 500 psi to obtain the membrane electrode.
[0041] Example 2
[0042] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the feeding amount of the higher alcohol and the aqueous solvent is adjusted so that the mass ratio of the higher alcohol to the aqueous solvent is 1:1. Specifically, according to the mass ratio, water: higher alcohol: dimethyl sulfoxide = 42.5:42.5:15. The rest of the raw material ratios and the preparation method are strictly consistent with those in Example 1, especially the feeding amount of dimethyl sulfoxide is strictly consistent with that in Example 1.
[0043] Example 3
[0044] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the feeding amount of the higher alcohol and the aqueous solvent is adjusted so that the mass ratio of the higher alcohol to the aqueous solvent is 7:1. Specifically, according to the mass ratio, water: higher alcohol: dimethyl sulfoxide = 10.625:74.375:15. The rest of the raw material ratios and the preparation method are strictly consistent with those in Example 1, especially the feeding amount of dimethyl sulfoxide is strictly consistent with that in Example 1.
[0045] Example 4
[0046] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the feeding amount of dimethyl sulfoxide is adjusted so that the mass of dimethyl sulfoxide: the sum of the mass of the aqueous solvent and the higher alcohol = 3:7, specifically, according to the mass ratio, water: higher alcohol: dimethyl sulfoxide = 14:56:30. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1, especially the mass ratio of the higher alcohol to the aqueous solvent is strictly consistent with that in Example 1.
[0047] Example 5
[0048] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the feeding amount of dimethyl sulfoxide is adjusted so that the mass of dimethyl sulfoxide: the sum of the mass of the aqueous solvent and the higher alcohol = 3:57 = 1:19, specifically, according to the mass ratio, water: higher alcohol: dimethyl sulfoxide = 19:76:5. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1, especially the mass ratio of the higher alcohol to the aqueous solvent is strictly consistent with that in Example 1.
[0049] Example 6
[0050] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that in the process of preparing the hydrogen production anode catalyst slurry, isopropanol of equal mass is used to replace the n-butanol in Example 1, that is, isopropanol is used as the higher alcohol. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0051] Example 7
[0052] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that in the process of preparing the hydrogen production anode catalyst slurry, an equal mass of n-pentanol is used to replace the n-butanol in Example 1, that is, n-pentanol is used as the higher alcohol. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0053] Example 8
[0054] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the feeding order of the catalyst and the anode catalyst is adjusted. The specific operation includes: firstly, the anode catalyst is mixed evenly with the solvent to obtain a first dispersion liquid, and then the first dispersion liquid is mixed evenly with the ionomer to obtain a second dispersion liquid. The rest of the raw material ratios and preparation methods are strictly consistent with Example 1.
[0055] Example 9
[0056] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the catalyst and the anode catalyst are mixed with the solvent at the same time. The specific operation includes: mixing the ionomer, the anode catalyst and the solvent evenly, shearing and cell crushing, and obtaining a third dispersion. The rest of the raw material ratios and preparation methods are strictly consistent with Example 1.
[0057] Example 10
[0058] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that during the preparation of the anode catalyst layer, the hydrogen production anode catalyst slurry is dried at 40° C. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0059] Embodiment 11
[0060] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that during the preparation of the anode catalyst layer, the hydrogen production anode catalyst slurry is dried at 50° C. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0061] Example 12
[0062] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that during the preparation of the anode catalyst layer, the hydrogen production anode catalyst slurry is dried at 80° C. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0063] Embodiment 13
[0064] This embodiment refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this embodiment and Example 1 is that during the preparation of the anode catalyst layer, the hydrogen production anode catalyst slurry is dried at 90° C. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1.
[0065] Comparative Example 1
[0066] This comparative example refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this comparative example and Example 1 is that in the process of preparing the hydrogen production anode catalyst slurry, an equal mass of ethanol is used to replace the n-butanol in Example 1. The rest of the raw material ratios and preparation methods are strictly consistent with Example 1.
[0067] Comparative Example 2
[0068] This comparative example refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this comparative example and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the feeding amount of dimethyl sulfoxide is adjusted so that the mass of dimethyl sulfoxide: the sum of the mass of the aqueous solvent and the higher alcohol = 4:6, specifically, according to the mass ratio, water: higher alcohol: dimethyl sulfoxide = 12:48:40. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1, especially the mass ratio of the higher alcohol to the aqueous solvent is strictly consistent with that in Example 1.
[0069] Comparative Example 3
[0070] This comparative example refers to the preparation method provided in Example 1 to prepare a membrane electrode. The difference between this comparative example and Example 1 is that: in the process of preparing the hydrogen production anode catalyst slurry, the feeding amount of dimethyl sulfoxide is adjusted so that the mass of dimethyl sulfoxide: the sum of the mass of the aqueous solvent and the higher alcohol = 3:67, specifically, according to the mass ratio, water: higher alcohol: dimethyl sulfoxide = 19.14: 76.57: 4.29. The rest of the raw material ratios and preparation methods are strictly consistent with those in Example 1, especially the mass ratio of the higher alcohol to the aqueous solvent is strictly consistent with that in Example 1.
[0071] Test Case
[0072] Test objects: the hydrogen production anode catalyst slurry, anode catalyst layer and membrane electrode prepared in Examples 1 to 13 and Comparative Examples 1 to 3.
[0073] Test items and test methods:
[0074] (1) Particle size distribution of slurry particles: The above hydrogen production anode catalyst slurry is tested for particle size by a laser particle size analyzer, and the particle sizes of the slurry particles in the upper, middle and lower layers of the hydrogen production anode catalyst slurry are recorded respectively, and the particle size standard deviation of the slurry particles in the hydrogen production anode catalyst slurry is calculated. When the particle size standard deviation is greater than 100, it is considered fair; when the particle size standard deviation is less than 100, it is considered good; when the particle size standard deviation is less than 50, it is considered excellent.
[0075] (2) Cracking of the anode catalyst layer: A metallographic microscope was used to observe the structure of the anode catalyst layer, the size and distribution of the cracks, and the image J software was used to record the crack rate of the anode catalyst layer. Figure 1 As shown, the bright area is shown in red (i.e. cracks), and the dark area is shown in gray (i.e. catalytic layer). Crack rate = bright area area / dark area area. When the crack rate is greater than 5%, it is considered fair; when the crack rate is less than 5%, it is considered good; when the crack rate is less than 2%, it is considered excellent.
[0076] (3) Ohmic resistance (HFR):
[0077] The membrane electrodes prepared in the above groups were assembled into a water electrolyzer with the cathode plate (with flow field), the anode plate (with flow field), the end plate and the insulating plate. Using an electrochemical workstation, the working electrode line WE and the working sensing electrode line WS were connected to the cathode side plate, and the reference electrode line RE and the auxiliary electrode CE line were connected to the anode side plate. The constant voltage AC impedance of the test object was tested at open circuit potential, with the high frequency set to 100000 Hz, the low frequency to 1 Hz, and the amplitude to 10 mV. After the test results were fitted, the ohmic impedance (HFR) value was recorded.
[0078] When HFR is less than 250mΩ*cm 2 When HFR is less than 200mΩ*cm 2 When HFR is less than 160mΩ*cm 2 When HFR is less than 130mΩ*cm 2 When it is considered excellent.
[0079] Test results: The test results are shown in Table 2. In addition, the metallographic microscope image of the anode catalyst layer provided in Example 1 is as follows: Figure 2 As shown, the metallographic microscope image of the anode catalyst layer provided in Example 9 is as follows Figure 3As shown, the metallographic microscope image of the anode catalyst layer provided in Comparative Example 1 is as follows Figure 4 shown.
[0080] Table 2. Test data obtained in this test case
[0081]
[0082] Result analysis:
[0083] By comparing the test performance of the hydrogen production anode catalyst slurry provided in Examples 1 to 13 with that provided in Comparative Examples 1 to 3 in the above table, it can be found that compared with the hydrogen production anode catalyst slurry provided in Comparative Examples 1 to 3, the anode catalyst layer prepared by the hydrogen production anode catalyst slurry provided in Examples 1 to 13 has a lower crack rate, and the hydrogen production of the membrane electrode is more stable, which is reflected in the lower ohmic impedance. Among all the above-mentioned test objects, the hydrogen production anode catalyst slurry provided in Example 1 has the best particle size dispersibility, and the prepared anode catalyst layer has the best structural stability and the smallest crack rate. The corresponding water electrolysis membrane electrode has the smallest ohmic impedance, which is even better than the ohmic impedance of the sprayed membrane electrode, and the water electrolyzer using the water electrolysis membrane electrode has good hydrogen evolution stability.
[0084] By comparing the hydrogen production anode catalyst slurry provided in Example 1, Examples 6 to 7 with Comparative Example 1, it can be found that when a higher alcohol having a carbon atom number of not less than 3 is mixed with an aqueous solvent and dimethyl sulfoxide as a solvent, the solvent volatilization can be improved, thereby reducing the membrane shrinkage caused by solvent volatilization, effectively improving the cracks in the anode catalyst layer, and improving the structural stability of the anode catalyst layer. Among them, the average particle size of the hydrogen production anode catalyst slurry provided in Example 1 is 498nm, and the standard deviation of the slurry particle size is 9. The average particle size of the hydrogen production anode catalyst slurry provided in Comparative Example 1 is 809nm, and the standard deviation of the slurry particle size is 121.
[0085] By comparing the hydrogen production anode catalyst slurries provided in Example 1 and Examples 4 to 5 with Comparative Examples 2 to 3, it can be found that when the mass ratio of higher alcohol to aqueous solvent in the hydrogen production anode catalyst slurry is 1 to 7:1, and the mass of dimethyl sulfoxide: the sum of the mass of aqueous solvent and higher alcohol = 3:7 to 57, the obtained anode catalyst layer has good structural stability and a small crack rate, and the membrane electrode using the anode catalyst layer has a smaller ohmic impedance.
[0086] By comparing the performance indicators provided in Example 1 with those provided in Examples 8 to 9, it can be found that the hydrogen production anode catalyst slurry prepared by the step-by-step feeding method of first dispersing the ionomer and then adding the anode catalyst has better dispersibility and fewer cracks in the anode catalyst layer. Among them, the average particle size of the hydrogen production anode catalyst slurry provided in Example 1 is 498nm, and the standard deviation of the slurry particle size is 9. The average particle size of the hydrogen production anode catalyst slurry provided in Example 9 is 914nm, and the standard deviation of the slurry particle size is 148.
[0087] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A hydrogen production anode catalyst slurry, characterized in that: It comprises an anode catalyst, an ionomer, and a solvent, wherein the solvent comprises an aqueous solvent, a higher alcohol and dimethyl sulfoxide, and the number of carbon atoms of the higher alcohol is not less than 3; The mass ratio of the higher alcohol to the aqueous solvent is 1-7:1, and the mass of the dimethyl sulfoxide: the sum of the mass of the aqueous solvent and the higher alcohol=3:7-57.
2. The hydrogen production anode catalyst slurry according to claim 1, characterized in that: The higher alcohol includes at least one of propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, benzyl alcohol, propylene glycol, glycerol and n-pentanol.
3. The hydrogen production anode catalyst slurry according to claim 1, characterized in that: The anode catalyst includes a substance containing at least one element of ruthenium, iridium, nickel, iron, cobalt, and manganese.
4. The hydrogen production anode catalyst slurry according to claim 1, characterized in that: The invention also includes additives, which include at least one of hydrolyzed polyacrylamide, polyethylene oxide, hydroxymethyl cellulose sodium salt and hydroxyethyl cellulose.
5. The hydrogen production anode catalyst slurry according to claim 1, characterized in that: The viscosity of the hydrogen production anode catalyst slurry is 10 to 200 cP.
6. The hydrogen production anode catalyst slurry according to any one of claims 1 to 5, characterized in that: The solid content of the hydrogen production anode catalyst slurry is 5 to 30 wt%.
7. A method for preparing anode catalyst slurry for hydrogen production according to any one of claims 1 to 6, characterized in that: The method comprises the following operations: firstly, the ionomer is uniformly mixed with the solvent to obtain a first dispersion, then the first dispersion is uniformly mixed with the anode catalyst, and after post-treatment, the hydrogen production anode catalyst slurry is obtained.
8. An anode catalyst layer, characterized in that: The anode catalyst layer is made from the hydrogen production anode catalyst slurry as claimed in any one of claims 1 to 7.
9. The anode catalyst layer according to claim 8, characterized in that: The method for preparing the anode catalyst layer comprises the following operations: coating the hydrogen production anode catalyst slurry on an anion exchange membrane and drying it at 50-80° C. to form the anode catalyst layer from the hydrogen production anode catalyst slurry.
10. A membrane electrode, characterized in that: It includes an anode gas diffusion layer, an anode catalyst layer, an anion exchange membrane, a cathode catalyst layer, and a cathode gas diffusion layer which are arranged in sequence; The anode catalyst layer comprises the anode catalyst layer according to any one of claims 8 to 9.